Assessing consumer welfare impacts of aviation policy measures - Guillaume Burghouwt (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2019)
Assessing the potential economic impacts of aviation policy measures is a recurrent topic. Examples of such policy measures are public investments in aviation infrastructure, the liberalisation of air transport markets, the introduction of aviation taxes or environmental restrictions on airport growth. In many countries, investments in aviation infrastructure are evaluated through Cost-Benefit Analysis (CBA) (e.g. CEPA, 2007; Decisio et al., 2014; Forsyth, 2013; Jorge and De Rus, 2004; UK Airports Commission, 2015). In addition, aviation policy measures/ reforms such as deregulation and environmental measures have been assessed using CBA/ welfare analysis (Booz, 2007; Forsyth, 2014a,b), although applications are less widespread.
Keywords: 330